Species Diversity of Shrimp Caught by Fishermen in the Buffer Zone of East Cost Mangrove Forest Nature Reserve, Jambi Province - Savitri, Ema; Nugraha, Anggit Prima; Hombing, Desi Natalia; Atika, Siti; Firdaus, Wildani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Buffer zone is an area surrounding a nature reserve that serves to protect the inner ecosystem from external influences. The East Coast Mangrove Forest Reserve is a nature conservation area located in Jambi Province. Both in the waters of Mendahara Ilir and Nipah Panjang, which are focused on preserving mangrove forest ecosystems. The method used is exploratory description and interviews with fishermen. The results obtained show that there are 11 speciesof shrimp found in the East Coast Mangrove Forest Reserve Area, namely: Galah Shrimp (Macrobrachium rosenbergii), Ketak Shrimp (Harpiosquilla raphidea), Hanging Shrimp (Macrobrachium nipponense), Striped Shrimp (Parapenaeopsis sculptilis), Peci Shrimp (Penaeus merguiensis), Lime Shrimp (Metapenaeus dobsoni), Agogo Shrimp (Penaeus indicus), Uka Shrimp (Metapenaeus brevicornis), Spur Shrimp (Palaemon styliferus), Ube Shrimp (Metapenaeus tenuipes) and Swallow Shrimp (Metapenaeus affinis). From the research that has been done, the data obtained that the speciesof shrimp in Nipah Panjang are more than the speciesof shrimp in Mendahra Ilir Village. One of the factors that cause differences in catches is the type of fishing gear used.